To Determng the Serostatus and Frequency of HIV Exposed Infants in Ishaka Adventist Hospital - B.M. Ambrose; G.O. Mauti; M. Nansunga; E.M. Mauti; B.M. Mabeya; G.R. Neel (Journal of Pharmacy and Nutrition Sciences, 2016)
Background: Acquired Immune deficiency syndrome was first reported in the United States in 1981 and has since become a major worldwide epidemic. An estimated 34 million people are living with HIV, according to UNAIDS estimates released early December 2011. This study determined the serostatus and frequency of ill health of HIV exposed infants in Ishaka Adventist hospital. Method: Study Design: The study design was descriptive cross sectional study to determine the serostatus and frequency of ill health among HIV exposed infants and the feeding options chosen by mothers. Study Population: The study focused on HIV exposed infants brought in the EID clinic from Bushenyi, Mitooma, Rubirizi, Sheema and Buhweju districts. According to the incharge EID clinic, the clinic gets about 10 patients per day and runs from Monday to Friday. The prevalence rate of HIV among mothers attending antenatal care in Bushenyi district is 7.2%. “Incharge EID clinic said” This gives a reflection of HIV exposed infants. The majority of people in Bushenyi district are small scale subsistence farmers, earning less than 1 dollar per day. The main cash crop is coffee and food crop is matooke. Other food crops include; Millet, cassava, potatoes, beans, groundnuts and peas. The animals kept mainly are; cows, goats, sheep and hens (District records 2014). Sampling Procedure: To determine the prevalence of HIV, a systematic random sampling method using EID numbers was used. To determine the feeding options and frequency of ill health, a ballot paper was used to determine the participants among the clients who attend to the clinic. Results: A total of 100 respondents were used. Majority of the mothers 51(51%) said PMTCT offers services like HIV counseling and Testing especially pregnant mothers for safe delivery after knowing your serostatus, 20 (20%) said it involves health education to pregnant mothers on safe motherhood, while minority 2(2%) said it involves breastfeeding, most of the mothers 80 (80%) had an idea about breast feeding options among mothers who are HIV positive, 4 (4%) were confused and16 (16%) did not know about any option. Majority of the mothers 55 (55%) said that ARV’s should be taken for PMTCT to be possible, 12(12%) said attending ANC and delivering in hospital, 17 (17 %) said feeding well, 2 (2%) said abstaining, and 2(2%) didn’t know.